High-temperature-resistant liquid crystal polyarylester and preparation method thereof

By introducing 2,6-naphthalene dicarboxylic acid and bisphenol fluorene with hockey structures, combined with monomers such as parabenzoic acid, high-temperature resistant liquid crystal polyaryl ester was designed, which solved the lack of heat resistance and processability of existing materials. The problem is that the melting point reduction, the glass transition temperature increase and the processability improvement are achieved, which is suitable for high-temperature environment applications.

CN119143978APending Publication Date: 2024-12-17NINGBO HIGLAR NEW MATERIAL TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411314929.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing liquid crystal polyaryl materials have insufficient heat resistance and processability, high melting point and narrow glass transition temperature, which limit their application and processing window in high temperature environments.

Method used

By introducing 2,6-naphthalene dicarboxylic acid with a hockey structure and bisphenol fluorene containing ether bonds as monomers, combined with parabenzoic acid, 4,4'-bifenol and terephthalic acid, a design was designed A high-temperature resistant liquid crystal polyarylene adopts monomer polymerization and melt polycondensation processes to adjust the molecular structure to reduce the melting point and increase the glass transition temperature.

Benefits of technology

It has achieved the reduction of the melting point of liquid crystal polyaryl, widens the processing temperature window, improves the toughness and processability of the material, enhances the heat resistance, and simplifies the production process, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143978A_ABST
    Figure CN119143978A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant liquid crystal polyarylester and a preparation method thereof, the liquid crystal polyarylester is formed by polymerizing monomers, and the monomers are composed of p-hydroxybenzoic acid HBA, 4, 4 '-biphenol BP, terephthalic acid TA, 2, 6-naphthalic acid NDA and 9, 9-bis [4-(4-methoxycarbonyl phenoxy) phenyl] fluorene; the corresponding molar ratio of the monomers is (50-60): (20-25): (5-10): (10-15): (1-5), and the sum of the molar ratios of the monomers is 100. By adding a small amount of 2, 6-naphthalic acid, the melting point Tm of LCP is reduced, the processing temperature window is widened, and processing is facilitated; by adding a small amount of bisphenol fluorene containing ether bonds, the toughness and processability of the LCP are improved while the glass-transition temperature Tg of the LCP is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyarylate preparation, and in particular to a high temperature resistant liquid crystal polyarylate and a preparation method thereof. Background Art

[0002] Liquid crystal polyarylate (LCP) is a polymer formed by connecting aromatic rings through ester bonds. Its molecular structure is different from the traditional random coil or cross-linked network structure. Its molecular structure is composed of long rigid rod-shaped molecular units connected together, and a liquid crystal phase is formed during heating. LCP exhibits the characteristics of high strength and high modulus, and has excellent thermal and mechanical properties. It is widely used in aerospace, electronics, and automobile manufacturing. However, with the advancement of science and technology and the expansion of application fields, higher requirements are placed on the heat resistance, processability, and comprehensive performance of polyarylate materials. Therefore, it is necessary to design the molecular structure of LCP, and to reduce the rigidity of its molecular chain as much as possible while ensuring that the liquid crystal phase is not destroyed, so as to reduce the melting point to an ideal range.

[0003] Commercially available TLCP is often divided into three types according to the heat deformation temperature under a load of 1.86MPa: high temperature resistant (Type I), medium temperature resistant (Type II) and low temperature resistant (Type IⅡ). About 60% of commercial TLCP fibers are made of Type II TLCP, and its glass transition temperature Tg is only between 70 and 150°C, which limits its application in high temperature environments. Type I TLCP has good heat resistance, but its basic structure is a para-substituted benzene ring, which is formed by the condensation of symmetrical rigid monomers, resulting in the melting point Tm of the polymer being too high and difficult to process. At the same time, the existing thermotropic liquid crystal polyarylates generally have the problem of difficult to control the polymerization reaction during preparation. The melting temperature of the thermotropic liquid crystal polyarylates finally obtained is very high, and the processing window is narrow, which to a certain extent limits its further expansion of applications. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the technical defects of the background technology, and provide a new method for improving the heat resistance of polyarylate materials and reducing their melting point by specific monomer combination and molecular structure design. The liquid crystal polyarylate of the present invention is polymerized by monomers, wherein the monomers are composed of p-hydroxybenzoic acid (HBA), 4,4'-biphenol (BP) and terephthalic acid (TA) as the main chain structure, and the monomers 2,6-naphthalene dicarboxylic acid (NDA) and bisphenol fluorene containing ether bonds with a hockey stick structure are introduced as raw materials; within a certain composition range, a small amount of 2,6-naphthalene dicarboxylic acid (NDA) is added, the melting point (Tm) of LCP is reduced, the processing temperature window is widened, and processing is facilitated; a small amount of bisphenol fluorene containing ether bonds is added, while the glass transition temperature (Tg) of LCP is increased, the toughness and processability of LCP are improved.

[0005] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0006] A high temperature resistant liquid crystal polyarylate, the liquid crystal polyarylate is prepared by polymerization of monomers, the monomers are composed of p-hydroxybenzoic acid (HBA), 4,4'-biphenol (BP), terephthalic acid (TA), 2,6-naphthalene dicarboxylic acid (NDA) and 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene; the corresponding molar ratio of the monomers is p-hydroxybenzoic acid (HBA): 4,4'-biphenol (BP): terephthalic acid (TA): 2,6-naphthalene dicarboxylic acid (NDA): 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene = (50-60): (20-25): (5-10): (10-15): (1-5), and the sum of the molar ratios of the monomers is 100;

[0007] The structural formula of the monomer 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene is:

[0008]

[0009] Preferably, the corresponding molar ratio of the monomers is p-hydroxybenzoic acid (HBA): 4,4'-biphenol (BP): terephthalic acid (TA): 2,6-naphthalene dicarboxylic acid (NDA): 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene=54:23:8:(10-12.5):(2.5-5).

[0010] More preferably, the corresponding molar ratio of the monomers is p-hydroxybenzoic acid (HBA):4,4'-biphenol (BP):terephthalic acid (TA):2,6-naphthalene dicarboxylic acid (NDA):9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene=54:23:8:10:5.

[0011] Preferably, the synthesis method of the monomer 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene is as follows:

[0012] Dissolve bisphenol fluorene (146 g, 0.42 mol) in a mixed solution of DMF and toluene, add anhydrous potassium carbonate (115 g, 0.8 mol) and heat under reflux to remove water and toluene; after the above reaction is completed, lower the system temperature to 60°C, add p-fluorobenzonitrile (102 g, 0.84 mol), then raise the system temperature to 150°C, react for 8 hours, filter and extract the generated white powdery crude product, purify it, wash it repeatedly with water and methanol solution, and dry it in vacuo; mix the obtained product with 45 g (0.8 mol) potassium hydroxide, ethanol and distilled water are mixed, heated under reflux until the solution becomes transparent and clear. After the reaction is completed, the solution is filtered while hot to remove impurities, and after cooling, it is acidified to pH = 2-3, and the precipitated white powder is separated by filtration and thoroughly washed with water and then vacuum dried; it is mixed with methanol and concentrated sulfuric acid and heated under reflux for reaction for 12 hours; after the reaction is completed, the obtained white crude product is filtered, extracted and purified, and repeatedly washed and vacuum dried to obtain 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene.

[0013] Preferably, bisphenol fluorene (146 g, 0.42 mol) is dissolved in a mixed solution of 700 ml DMF and 700 ml toluene.

[0014] Preferably, the generated white powdery crude product is filtered, extracted and purified, then repeatedly washed with water and methanol solution, and dried in vacuo; the obtained product is mixed with 45 g (0.8 mol) potassium hydroxide, 300 mL ethanol and 200 mL distilled water.

[0015] Preferably, the precipitated white powder is separated by filtration, washed thoroughly with water and then dried under vacuum; the powder is mixed with 600 ml of methanol and 30 ml of concentrated sulfuric acid and heated under reflux for 12 h.

[0016] The preparation steps of the high temperature resistant liquid crystal polyarylate as described above include the following steps:

[0017] Parahydroxybenzoic acid (HBA), 4,4'-biphenol (BP), terephthalic acid (TA), 2,6-naphthalene dicarboxylic acid (NDA), 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene and acetic anhydride are added to a Hastelloy polymerization kettle for acetylation first, then slowly heated to 350°C and kept in vacuum for 0.5 to 1.5 hours, and then nitrogen is filled into the Hastelloy polymerization kettle for melt polycondensation, and the prepolymer is discharged from the Hastelloy polymerization kettle, crushed and dried to obtain a liquid crystal polyarylate prepolymer.

[0018] In the above technical solution, the reactive monomer and the acetylation agent are reacted in one pot to obtain the liquid crystal polyarylate prepolymer.

[0019] Preferably, the amount of acetic anhydride added is 1.5 to 3.0 times the total molar number of the five monomer hydroxyl groups, more preferably 2 times; when the amount of acetic anhydride added is less than 1.5, the degree of polymerization is low, the viscosity of the formed polymer is low, the fiber will break during spinning, and carbonization will occur when the spinning temperature is high, so it is difficult to fiberize; when the amount of acetic anhydride added exceeds 3.0, excess acetic anhydride remains on the surface of the polymer resin and generates gas, which causes the fiber to break easily during spinning.

[0020] Preferably, the acetylation and melt polycondensation are carried out under a nitrogen atmosphere, first heating to 120-160°C for reaction for 3-5h; then slowly heating to 260-280°C at a rate of 3-4°C / min for reaction for 1.5-3h, slowly heating at 280-300°C for reaction for 1-2h, slowly heating at 300-320°C for reaction for 1-2h, slowly heating at 320-350°C for reaction for 1-2h, then vacuum-insulating at 350°C for 0.5-1.5h; acetylation reaction is carried out at a temperature of 120-160°C; and melt polycondensation reaction is carried out at a temperature of 260-350°C.

[0021] More preferably, the acetylation and melt polycondensation are carried out under a nitrogen atmosphere, first heating to 140°C for reaction for 4 hours; then slowly heating to 260°C-280°C at a rate of 3.5°C / min for reaction for 3 hours, slowly heating at 280-300°C for reaction for 1.5 hours, slowly heating at 300-320°C for reaction for 1.5 hours, slowly heating at 320-350°C for reaction for 1.5 hours, and then keeping warm at 350°C in vacuum for 1 hour.

[0022] Preferably, the prepolymer needs to be completely crushed after being taken out and vacuum dried at 70°C for 8 hours; after the melt polycondensation is completed, the reaction product is vacuumed to further discharge small molecules, and acetic acid is collected as a polycondensation by-product; in the early stage of the reaction, a lower temperature can induce the reaction, and the molecular chain can be further grown by slowly increasing the temperature, and finally a thermotropic liquid crystal polyarylate with a high molecular weight, excellent molding and processing performance, and good thermal stability is obtained.

[0023] The preparation steps of the high temperature resistant liquid crystal polyarylate as described above include the following steps:

[0024] The obtained prepolymer is subjected to solid phase polymerization reaction in a nitrogen oven at 290-310° C. under a nitrogen atmosphere to obtain a liquid crystal polyarylate;

[0025] Preferably, the solid phase polymerization requires placing the crushed and dried prepolymer in a nitrogen atmosphere, heating it to 290-310° C. and reacting it for 3 hours to obtain liquid crystal polyarylate; the drying condition is vacuum drying at 70° C. for 8 hours.

[0026] The liquid crystal polyarylate structure of the present invention is further described as follows:

[0027] After the polycondensation reaction, the structural units derived from p-hydroxybenzoic acid (HBA), terephthalic acid (TA), 4,4'-biphenol (BP), 2,6-naphthalene dicarboxylic acid (NDA), and 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene in the prepolymer appear in the chain structure of the liquid crystal prepolymer molecule in the form of the following residues, with the hydroxyl group losing H and the carboxyl group losing OH:

[0028]

[0029] The principle of the present invention is further described as follows:

[0030] The present invention reduces the melting point of liquid crystal polyester by introducing a naphthalene ring nonlinear monomer 2,6-naphthalenedicarboxylic acid (NDA) with a hockey stick structure. The side-step translation effect of the 2,6-functional group substitution on the naphthalene ring enables the monomer to act as a "twist machine axis" to link the polyester molecular chains, thereby destroying the linear structure of the molecular chains, significantly reducing the Tm of the LCP, broadening the processing temperature window, and facilitating processing.

[0031] The unique Cardo skeleton structure and a large number of benzene rings of bisphenol fluorene increase the rigidity of the material molecular chain. The presence of ether bonds increases the flexibility of the material main chain, improving the heat resistance of the material while balancing the toughness and processability of the material. Therefore, the present invention is based on bisphenol fluorene with a Cardo skeleton, and designs and synthesizes a dibasic ester monomer with a flexible ether bond. The benzene rings are connected by ether bonds to achieve the effect of combining rigidity and flexibility.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The present invention uses p-hydroxybenzoic acid (HBA), 4,4'-biphenol (BP) and terephthalic acid (TA) as the main chain structure, introduces 2,6-naphthalene dicarboxylic acid (NDA) with a hockey stick structure and bisphenol fluorene containing an ether bond as raw materials, utilizes the "side step" effect of the naphthalene ring structure of NDA and the unique Cardo skeleton structure and a large number of benzene rings of bisphenol fluorene, and combines the introduction of flexible ether bonds to achieve the following purposes:

[0034] (1) Lowering the melting point and increasing the glass transition temperature: The monomer 2,6-naphthalene dicarboxylic acid (NDA) with a hockey stick structure can, to a certain extent, destroy the linear structure of the rigid molecular chain and reduce the regularity of the main molecular chain, ultimately achieving the purpose of reducing the Tm of the polyarylate, thereby effectively improving the processability; the unique Cardo skeleton structure and a large number of benzene rings of bisphenol fluorene can significantly enhance the rigidity of the molecular chain and improve the heat resistance of the material;

[0035] (2) Combining rigidity and flexibility to improve spinnability: The unique rigid structure of bisphenol fluorene improves the heat resistance of the material while also affecting its processability. Therefore, the ether bond between the benzene rings plays a role in combining rigidity and flexibility, reducing the linearity of the macromolecule while also acting as a plasticizer, achieving a good balance between heat resistance and processability.

[0036] (3) Reduce costs and facilitate industrialization: The raw materials of the present invention are easily available and the synthesis process is simple. The liquid crystal polyarylate is prepared by a one-pot reaction, that is, the acetylation reaction and the melt polycondensation reaction are carried out in sequence in one reactor, thereby avoiding the long process and high pollutant emission problems of the acetylation process in the "two-step method", thereby shortening the production cycle, improving production efficiency, and being suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the synthesis process of 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene described in Examples 1 to 5 of the present invention. DETAILED DESCRIPTION

[0038] In order to better understand the content of the present invention, further description is given below in conjunction with specific embodiments and accompanying drawings. It should be understood that these embodiments are only used to further illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content described in the present invention, those skilled in the art may make some non-essential changes or adjustments to the present invention, which still belong to the protection scope of the present invention.

[0039] The synthesis process of 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene of the present invention is as follows Figure 1 As shown, the specific method is as follows:

[0040] Dissolve bisphenol fluorene (146 g, 0.42 mol) in a mixed solution of 700 ml DMF and 700 ml toluene, add anhydrous potassium carbonate (115 g, 0.8 mol) and heat under reflux to remove water and toluene; after the above reaction is completed, lower the system temperature to 60°C, add p-fluorobenzonitrile (102 g, 0.84 mol), then raise the system temperature to 150°C, react for 8 hours, filter and extract the generated white powdery crude product, purify it, wash it repeatedly with water and methanol solution, and dry it in vacuo; mix the obtained product with 45 g (0.8 mol) potassium hydroxide, 300 mL ethanol and 2 00mL of distilled water, heated to reflux until the solution becomes transparent and clear. After the reaction is completed, the above solution is filtered while hot to remove impurities. After cooling, it is acidified to pH = 2-3, and the precipitated white powder is separated by filtration and thoroughly washed with water and then vacuum dried; it is mixed with 600mL of methanol and 30mL of concentrated sulfuric acid and heated to reflux for reaction for 12h; after the reaction is completed, the obtained white crude product is filtered, extracted and purified, and repeatedly washed and vacuum dried to obtain 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene.

[0041] Example 1

[0042] The preparation method of the liquid crystal polymer in this example is as follows:

[0043] 74.52 g (0.54 mol) of p-hydroxybenzoic acid (HBA), 42.78 g (0.23 mol) of 4,4'-biphenol (BP), 13.28 g (0.08 mol) of terephthalic acid (TA), 27 g (0.125 mol) of 2,6-naphthalenedicarboxylic acid (NDA), 12.075 g (0.025 mol) of 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene and 204 g (2 mol) of acetic anhydride were weighed and added into a Hastelloy polymerization reactor and heated at 140 ℃, reflux for 4h for acetylation, slowly heat to 260℃ at a rate of 3.5℃ / min, slowly heat at 260-280℃ for 3h, slowly heat at 280-300℃ for 1.5h, slowly heat at 300-320℃ for 1.5h, slowly heat at 320-350℃ for 1.5h. The whole reaction is carried out under nitrogen atmosphere, and the by-product acetic acid is distilled off at the same time. Then, it is vacuum-insulated at 350℃ for 1h. After the reaction is completed, it is discharged through a Hastelloy polymerization kettle and crushed to obtain liquid crystal polyarylate.

[0044] Example 2

[0045] The preparation method of the liquid crystal polymer in this example is as follows:

[0046] 74.52 g (0.54 mol) of p-hydroxybenzoic acid (HBA), 42.78 g (0.23 mol) of 4,4'-biphenol (BP), 13.28 g (0.08 mol) of terephthalic acid (TA), 21.6 g (0.1 mol) of 2,6-naphthalenedicarboxylic acid (NDA), 24.15 g (0.05 mol) of 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene and 204 g (2 mol) of acetic anhydride were weighed and added into a Hastelloy polymerization reactor and heated at 140 ℃, reflux for 4h for acetylation, slowly heat to 260℃ at a rate of 3.5℃ / min, slowly heat at 260-280℃ for 3h, slowly heat at 280-300℃ for 1.5h, slowly heat at 300-320℃ for 1.5h, slowly heat at 320-350℃ for 1.5h. The whole reaction is carried out under nitrogen atmosphere, and the by-product acetic acid is distilled off at the same time. Then, it is vacuum-insulated at 350℃ for 1h. After the reaction is completed, it is discharged through a Hastelloy polymerization kettle and crushed to obtain liquid crystal polyarylate.

[0047] Example 3

[0048] The preparation method of the liquid crystal polymer in this example is as follows:

[0049] 74.52 g (0.54 mol) of p-hydroxybenzoic acid (HBA), 42.78 g (0.23 mol) of 4,4'-biphenol (BP), 13.28 g (0.08 mol) of terephthalic acid (TA), 21.6 g (0.1 mol) of 2,6-naphthalenedicarboxylic acid (NDA), 24.15 g (0.05 mol) of 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene, and 204 g (2 mol) of acetic anhydride were added to a Hastelloy polymerization reactor, and the mixture was refluxed at 140°C for 4 h for acetylation. The temperature was slowly increased to 260°C at a rate of ℃ / min, and the reaction was slowly heated at 260-280°C for 3h, slowly heated at 280-300°C for 1.5h, slowly heated at 300-320°C for 1.5h, and slowly heated at 320-350°C for 1.5h. The entire reaction was carried out under a nitrogen atmosphere, and the by-product acetic acid was distilled off. Subsequently, the mixture was vacuum-insulated at 350°C for 1h. After the reaction was completed, the polymer was poured out, crushed, placed in a vacuum oven at 70°C for 8h, and then added to a Hastelloy polymerization kettle. Solid-phase polymerization was carried out at 290°C for 3h under a nitrogen atmosphere to obtain liquid crystal polyarylate.

[0050] Example 4

[0051] The preparation method of the liquid crystal polymer in this example is as follows:

[0052] Weigh (74.52g (0.54mol) of p-hydroxybenzoic acid (HBA), 42.78g (0.23mol) of 4,4'-biphenol (BP), 13.28g (0.08mol) of terephthalic acid (TA), 21.6g (0.1mol) of 2,6-naphthalenedicarboxylic acid (NDA), 24.15g (0.05mol) of 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene, 204g (2mol) of acetic anhydride into a Hastelloy polymerization reactor, react at 70°C for 4h for acetylation, and heat for 3.5 The temperature was slowly increased to 260°C at a rate of ℃ / min, and the reaction was slowly heated at 260-280°C for 3h, slowly heated at 280-300°C for 1.5h, slowly heated at 300-320°C for 1.5h, and slowly heated at 320-350°C for 1.5h. The entire reaction was carried out under a nitrogen atmosphere, and the by-product acetic acid was distilled off. Subsequently, the mixture was vacuum-insulated at 350°C for 1h. After the reaction was completed, the polymer was poured out, crushed, placed in a vacuum oven at 70°C for 8h, and then added to a Hastelloy polymerization kettle. Solid-phase polymerization was carried out at 300°C for 3h under a nitrogen atmosphere to obtain liquid crystal polyarylate.

[0053] Example 5

[0054] The preparation method of the liquid crystal polymer in this example is as follows:

[0055] 74.52 g (0.54 mol) of p-hydroxybenzoic acid (HBA), 42.78 g (0.23 mol) of 4,4'-biphenol (BP), 13.28 g (0.08 mol) of terephthalic acid (TA), 21.6 g (0.1 mol) of 2,6-naphthalenedicarboxylic acid (NDA), 24.15 g (0.05 mol) of 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene, and 204 g (2 mol) of acetic anhydride were added to a Hastelloy polymerization reactor, and the mixture was refluxed at 140°C for 4 h for acetylation. The temperature was slowly increased to 260°C at a rate of ℃ / min, and the reaction was slowly heated at 260-280°C for 3h, slowly heated at 280-300°C for 1.5h, slowly heated at 300-320°C for 1.5h, and slowly heated at 320-350°C for 1.5h. The entire reaction was carried out under a nitrogen atmosphere, and the by-product acetic acid was distilled off. Subsequently, the mixture was vacuum-insulated at 350°C for 1h. After the reaction was completed, the polymer was poured out, crushed, placed in a vacuum oven at 70°C for 8h, and then added to a Hastelloy polymerization kettle. Solid-phase polymerization was carried out at 310°C for 3h under a nitrogen atmosphere to obtain liquid crystal polyarylate.

[0056] Comparative Example 1

[0057] The preparation method of the liquid crystal polymer in this example is as follows:

[0058] 41.4 g (0.3 mol) of p-hydroxybenzoic acid (HBA), 18.6 g (0.1 mol) of 4,4'-biphenol (BP), 16.6 g (0.1 mol) of terephthalic acid (TA), and 102 g (1 mol) of acetic anhydride were weighed and added to a Hastelloy alloy polymerization kettle, and the mixture was refluxed at 140°C for 4 h for acetylation. The mixture was slowly heated to 260°C at a rate of 3.5°C / min, and the mixture was slowly heated at 260-280°C for 3 h, at 280-300°C for 1.5 h, and at 300-320°C for 1.5 h. The entire reaction was carried out under a nitrogen atmosphere, and the by-product acetic acid was distilled off at the same time. After the reaction was completed, the mixture was discharged from the Hastelloy alloy polymerization kettle and crushed to obtain liquid crystal polyarylate.

[0059] The thermotropic liquid crystal polyarylates prepared in Examples 1 to 5 and Comparative Example 1 were subjected to performance tests in the following manner. The test results are shown in Table 1:

[0060] (1) Differential Scanning Calorimetry (DSC)

[0061] The melting point of liquid crystal polyarylate was tested using a DSC214Polyma differential scanning calorimeter. 5-10 mg of liquid crystal polyarylate sample was weighed and placed in an aluminum crucible for sample preparation, with an empty crucible as a reference. The atmosphere was nitrogen, the test temperature range was 20-400°C, the heating rate was 20°C / min, and the melting temperature of the sample was measured by two heatings and two coolings.

[0062] (2) Dynamic Mechanical Analysis (DMA)

[0063] The glass transition temperature of liquid crystal polyarylate was tested by DMA8000.

[0064] (3) Thermogravimetric analysis (TGA) test

[0065] Thermogravimetric analysis was performed using a TG209F1 NETZSCH thermogravimetric analyzer. 5-10 mg of polyarylate sample was weighed and added to a crucible, the heating rate was selected to be 20°C / min, the temperature range was 30-800°C, the test atmosphere was air, and the temperature at which the weight loss was 5% was recorded.

[0066] Table 1 Performance test results of thermotropic liquid crystal polyarylate prepared in Examples 1 to 5 and Comparative Example 1

[0067]

[0068] The above description is not intended to limit the present invention, and the present invention is not limited to the above examples. Any changes, modifications, additions or substitutions made by a person skilled in the art within the spirit and scope of the present invention shall also fall within the protection scope of the present invention.

Claims

1. A high temperature resistant liquid crystal polyarylate, It is characterized in that The liquid crystal polyarylate is prepared by polymerization of monomers, wherein the monomers are composed of p-hydroxybenzoic acid HBA, 4,4'-biphenyl BP, terephthalic acid TA, 2,6-naphthalene dicarboxylic acid NDA and 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene; the corresponding molar ratio of the monomers is p-hydroxybenzoic acid HBA: 4,4'-biphenyl BP: terephthalic acid TA: 2,6-naphthalene dicarboxylic acid NDA: 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene = (50-60): (20-25): (5-10): (10-15): (1-5), and the sum of the molar ratios of the monomers is 100; The structural formula of the monomer 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene is:

2. The high temperature resistant liquid crystal polyarylate according to claim 1, It is characterized in that The corresponding molar ratio of the monomers is p-hydroxybenzoic acid HBA:4,4'-biphenyl BP:terephthalic acid TA:2,6-naphthalene dicarboxylic acid NDA:9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene=54:23:8:(10-12.5):(2.5-5).

3. The high temperature resistant liquid crystal polyarylate according to claim 1, It is characterized in that The synthesis method of the monomer 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene is as follows: 0.42 mol of bisphenol fluorene was dissolved in a mixed solution of DMF and toluene, and 0.8 mol of anhydrous potassium carbonate was added and heated to reflux to remove water and toluene; after the above reaction was completed, the system temperature was lowered to 60°C, 0.84 mol of p-fluorobenzonitrile was added, and then the system temperature was raised to 150°C for reaction for 8 hours, and the generated white powdery crude product was filtered, extracted and purified, and then repeatedly washed with water and methanol solution, and vacuum dried; the obtained product was mixed with 0.8 mol of potassium hydroxide, ethanol and distilled water, and heated to reflux until the solution became transparent and clear. After the reaction was completed, the above solution was filtered while hot to remove impurities, and after cooling, it was acidified to pH = 2-3, and the precipitated white powder was separated by filtration and thoroughly washed with water and then vacuum dried; it was mixed with methanol and concentrated sulfuric acid and heated to reflux for reaction for 12 hours; after the reaction was completed, the obtained white crude product was filtered, extracted and purified, and repeatedly washed, and vacuum dried to obtain 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene.

4. A method for preparing a high temperature resistant liquid crystal polyarylate according to claim 1, It is characterized in that The steps include: Parahydroxybenzoic acid HBA, 4,4'-biphenyl BP, terephthalic acid TA, 2,6-naphthalene dicarboxylic acid NDA, 9,9-bis[4-(4-methoxycarbonylphenoxy)phenyl]fluorene and acetic anhydride are added to a Hastelloy polymerization kettle for acetylation first, then slowly heated to 350°C and kept in vacuum for 0.5 to 1.5 hours, and then nitrogen is filled into the Hastelloy polymerization kettle for melt polycondensation, and the prepolymer is discharged from the Hastelloy polymerization kettle, crushed and dried to obtain a liquid crystal polyarylate prepolymer.

5. A method for preparing a high temperature resistant liquid crystal polyarylate according to claim 4, It is characterized in that The amount of acetic anhydride added is 1.5 to 3.0 times the total molar number of the five monomer hydroxyl groups.

6. A method for preparing a high temperature resistant liquid crystal polyarylate according to claim 4, It is characterized in that The acetylation and melt polycondensation are carried out under a nitrogen atmosphere, firstly heating to 120-160°C for reaction for 3-5h; then slowly heating to 260-280°C at a rate of 3-4°C / min for reaction for 1.5-3h, slowly heating at 280-300°C for reaction for 1-2h, slowly heating at 300-320°C for reaction for 1-2h, slowly heating at 320-350°C for reaction for 1-2h, and then keeping warm at 350°C in vacuum for 0.5-1.5h.

7. A method for preparing a high temperature resistant liquid crystal polyarylate according to claim 6, Features The acetylation and melt polycondensation are carried out under a nitrogen atmosphere, firstly heating to 140°C for reaction for 4 hours; then slowly heating to 260°C-280°C at a rate of 3.5°C / min for reaction for 3 hours, slowly heating at 280-300°C for reaction for 1.5 hours, slowly heating at 300-320°C for reaction for 1.5 hours, slowly heating at 320-350°C for reaction for 1.5 hours, and then keeping warm at 350°C in vacuum for 1 hour.

8. A method for preparing a high temperature resistant liquid crystal polyarylate according to claim 4, It is characterized in that The prepolymer was completely crushed after being taken out and vacuum dried at 70° C. for 8 h.

9. A method for preparing a high temperature resistant liquid crystal polyarylate according to claim 4, It is characterized in that The preparation method comprises the following steps: The obtained prepolymer was subjected to solid phase polymerization reaction in a nitrogen oven at 290-310° C. under a nitrogen atmosphere to prepare a liquid crystal polyarylate.

10. A method for preparing a high temperature resistant liquid crystal polyarylate according to claim 9, It is characterized in that The solid phase polymerization reaction time is 3 hours.

Citation Information

Cited By

  • Method for preparing biphenol type high-heat-resistance liquid crystal polyester through melt coupling solid-phase polycondensation

    CN119708449A

  • Preparation method and application of high-temperature-resistant transparent modified polyester

    CN120309909A